0198 Lung Cancer Risk among Minnesota Taconite Mining Workers. (23rd June 2014) - Allen, Elizabeth; Alexander, Bruce; Mandel, Jeffrey; MacLehose, Richard; Ramachandran, Gurumurthy
Abstract : Objectives: The mining and processing of taconite results in exposures to non-asbestiform amphibole and non-amphibole minerals. Previous studies have shown that taconite mining workers are at an increased risk for developing lung cancer and mesothelioma and duration of employment has been shown to contribute to the risk of mesothelioma incidence. The objective of this analysis is to examine the relationship between duration of employment and lung cancer among Minnesota taconite workers. Method: Among a cohort of 44 243 taconite workers, 1721 cases of lung cancer were identified and matched by five-year age interval to two controls. Total duration of employment was abstracted from individual work records. Results: Among the 5159 workers included in the analysis, 55% worked less than one year and 15% worked 1–5 years, 5–15 years and more than 15 years. The mean duration of employment among cases and controls was 6.7 and 7.2 years respectively. A conditional logistic regression analysis did not show an increased risk for development of lung cancer among those who worked 1–5 years (OR = 1.2, 95% CI: 0.99, 1.38), 5–15 years (OR = 0.94, 95% CI: 0.79, 1.11), and more than 15 years (OR = 0.90, 95% CI: 0.75, 1.08) as compared to those who worked less than one year. Conclusions: Risk for development of lung cancer does not appear to be associated with duration of employment in the taconite industry. Future analyses will explore specific exposures to airborne particulates, including silica and non-asbestiform amphiboles, in this population.